2017
DOI: 10.1089/cap.2016.0031
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Acute-Onset Subtypes in Pediatric Obsessive-Compulsive Disorder

Abstract: A small yet significant percentage of pediatric OCD outpatients met criteria for PANDAS and/or PANS, justifying routine screening and attention to related characteristics during assessment and management. Longitudinal studies of these putative subtypes are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…To resolve the diagnostic issue, it was hypothesized that PANDAS constitutes a subtype of children's OCD, with the etiology of GAS infection. The legitimacy of PANDAS as a subgroup of OCD was supported by the study performed by Jaspers-Fayer et al in 2017 [34].…”
Section: Pandas and Ocd-where Is The Line?mentioning
confidence: 92%
“…To resolve the diagnostic issue, it was hypothesized that PANDAS constitutes a subtype of children's OCD, with the etiology of GAS infection. The legitimacy of PANDAS as a subgroup of OCD was supported by the study performed by Jaspers-Fayer et al in 2017 [34].…”
Section: Pandas and Ocd-where Is The Line?mentioning
confidence: 92%
“…focused on children (18,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and only one article had the required information for metaanalysis (18). Hence, we could not perform a child-specific meta-analysis.…”
Section: Of the 94 Articles That Investigated An Association Between mentioning
confidence: 99%
“…articles discussing this association (19,22,25,27,30,32,35,(37)(38)(39)(40)(41), of which 6 focused on children (22,25,27,30,32,35). Only one of these 12 articles was suitable for meta-analysis although there did appear to be an association between OCD and LUTS based on the content.…”
Section: Association Of Luts and Ocdmentioning
confidence: 99%
“…It is one of the rare clearly identified etiological factors of OCD. About 5% of pediatric OCD patients meet the criteria for PANDAS (or PANS) [117] and it is important to distinguish this etiology from others in OCD patients. Indeed, the prognosis of PANDAS seems relatively good, as Leon et al found that 88% of children originally suffering from PANDAS with moderate-to-severe OCD presented no OCD symptoms (55%) or only subclinical symptoms (33%) after approximately three years of follow-up [118] (Table 5).…”
Section: Infections and Ocdmentioning
confidence: 99%
“…By contrast, 48% of OCD patients were found to be still symptomatic after 30 years [119]. However, as this study began in 1954, and PANDAS patients, which represent about 5% of OCD patients, were first described in 1998 [105,117], one may hypothesize that PANDAS and non-PANDAS OCD patients were pooled together. Furthermore, treatment of PANDAS (described below) is not identical to OCD treatment.…”
Section: Infections and Ocdmentioning
confidence: 99%